Opportunities and Challenges for Informal Sector Economic Development: The Case of Street Vendors in Makassar City - Ahmadin; Misbawati (Jurnal Ekonomi dan Riset Pembangunan, 2024)
The informal sector is an integral part of the long journey of the economic development system in Indonesia, starting from the beginning of the national development period. The existence of the informal sector presents two sides of the community's economic conditions, namely creating a variety of very large jobs and becoming a solution to the problem of unemployment. However, on the other hand, it leaves various problems, especially in urban areas. This paper discusses the opportunities and challenges of economic development in the informal sector with the unit of analysis being Makassar city, South Sulawesi province. This type of research is qualitative both in terms of data and analysis. Data collection techniques were conducted through observation, interviews, and documentation. The results showed that the informal economy sector in Makassar city, as in other cities in Indonesia, experienced a significant increase. It's just that the policy regulation system and the lack of awareness of citizens, causing chaos from the operational aspects. One of the classic problems of the informal sector is the problem of urban space, such as: unclear status of jaulan places, evictions, and others.